THE USE OF DICTOGLOSS TECHNIQUE TO IMPROVE STUDENTS’ ABILITY IN WRITING RECOUNT TEXT OF FIRST GRADE AT SMK NEGERI 1 TOLITOLI - Moh Firmansyah (Jurnal Madako Education, 2018)
The objective of this research was to find out whether the application of dictogloss  technique improve the students’ writing recount text or not. It was a pre-experimental research. It was conducted at first grade of SMK Negeri 1 Tolitoli that was (X FM 1). The researcher gave a pre-test to measure the students’ previous ability in writing recount text. Then, a post-test was to find out the students’ writing recount text after given treatment which is the application of dictogloss technique. The researcher used SPSS 16.0 program to analyze the data collection. The result of data analysis showed that dictogloss technique give a significant effect to the students in writing a recount text. The mean score of the post-test (81,47) was higher than the mean score of pre-test (56,22). Then, the testing hypothesis showed that the value of tcount was greater than ttable (9,683 ≥ 2.040). In conclusion, the application of dictogloss technique is effective to improve students’ writing in recount text. Key words: Improve, Writing Ability, and Dictogloss Technique.